Japanese economic development : - Yoshihara, Kunio (Oxford University press, 1986)
This study provides a short, non-technical introduction to Japanese economic development. Emphasising the importance of non-economic factors as well as Japan's institutions and social structure, this work is ideal reading for those who wish to understand the secret of Japan's success in the world market today...